Implementation of Participatory Data-Based Planning (PDB) in Annual Planning at Primary Schools: Challenges and Impact - Irmayani; Kusumaningsih, Widya; Nurkolis (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the implementation of participatory data-based planning (PDB) in the annual planning process at SD Negeri Ungaran 02, Semarang Regency. Using a descriptive qualitative approach with a case study design, this research examines how educational reports are utilized in planning, the role of various stakeholders in the process, and the impact of this approach on improving the quality of education at the school. Data was collected through interviews with the school principal, teachers, school committee members, and parents, as well as through observations and document reviews. The findings reveal that the participatory process of identifying educational reports and involving multiple stakeholders has led to improvements in students' literacy and numeracy skills. However, challenges such as achievement gaps between classes and the limited use of technology in teaching remain. The reflection process on educational reports also highlighted issues such as low parental involvement and variations in teaching quality across classes. While the participatory approach to developing the Annual Work Plan (RKT) ensures broad stakeholder support and alignment with students' needs, the findings indicate that further efforts are needed to address challenges related to parental involvement and the integration of technology in teaching. This study concludes that participatory data-based planning is a crucial strategy for enhancing educational quality, but a more comprehensive approach is required to overcome existing barriers, such as maximizing the use of technology and improving teaching quality consistently across classes. Recommendations are provided for the Department of Education, the school, and teachers to improve the effectiveness of PDB implementation and educational outcomes.